Toxic Warfare - Karasik, Theodore W. (RAND Corporation, 2002)
The past several years have seen an increase in the use of toxic weapons -- i.e., inexpensive and easily acquired chemicals and industrial waste -- on the part of state as well as nonstate actors. Nonetheless, little analysis has been done on the nature and extent of this threat either to the military or to the U.S. homeland. This report examines the implications of toxic weapon use for military planning and concludes that such weapons merit further analysis.